Production Budget for Tomatoes in the Manatee-Ruskin Area of Florida - John VanSickle; Scott Smith; Eugene McAvoy (EDIS)
FE817, a 6-page fact sheet by John VanSickle, Scott Smith, and Eugene McAvoy, highlights tomato production in the Manatee-Ruskin Area, with a per-acre composite budget for a representative grower. Includes references. Published by the UF Department of Food and Resource Economics, December 2009.